Posharvest oxidative stress in horticulturral crops (Food Products Press, 2003)
This valuable book brings together internationally respected authorities who share their experiences, insights, and approaches to postharvest oxidative stress on fruits and vegetables. It explores the impact of various storage temperatures and atmospheres, looks at senescence dynamics and scald, and examines antioxidants and the regulation of active oxygen species production. You'll also learn about technologies that can enhance resistance to oxidative stress—physical treatments, chemical treatments, and genetic engineering.